اعلية الوحدات التدريبية في التركيز والانتباه وعلاقتها باتخاد القرار الصحيح في عملية التهديف لدى لاعبي كرة السلة - بوساح علاء الدين /زكاري سفيان (Institut d’Éducation Physique et Sportive / UNIVERSITY OF MOSTAGANEM, 2025)
تهدف هذه الدراسة الى بحث فاعلية استخدام وحدات تدريبية متخصصة في تحسين مستويات التركيز والانتباه لدى لاعبي كرة السلة الناشئين (تحت 17 سنة)، والكشف عن العلاقة بين هذه المهارات المعرفية وقدرتهم على اتخاذ القرارات الصائبة اثناء عملية التهديف تعتبر كرة السلة من الرياضات التي تتطلب تركيزا عاليا وقدرة على الانتباه للتفاصيل المتغيرة في الملعب بالإضافة الى السرعة البديهية في اتخاذ القرارت المناسبة في لحظات حاسمة. ومن هنا،تأتي أهمية تطوير هذه الجوانب المعرفية لدى اللاعبين الناشئين تعتمد الدراسة على تصميم تجريبي يتضمن مجموعتين مجموعة تجريبية تتلقى وحدات تدريبية تركز على تحسين التركيز والانتباه ومجموعة ضابطة تتبع برنامج التدريب الاعتيادي. يتم قياس مستويات التركيز والانتباه باستخدام اختبارات معيارية قبل وبعد تطبيق الوحدات التدريبة. تسعى الدراسة للإجابة على التساؤلات التالية: هل يؤدي تطبيق وحدات تدريبية متخصصة الى تحسين مستويات التركيز والانتباه لدى لاعبي كرة السلة الناشئين تحت 17 سنة؟ وهل توجد علاقة إيجابية بين مستويات التركيز والانتباه وقدرة اللاعبين على اتخاذ القرارات الصائبة في التهديف؟ من المتوقع ان تسفر نتائج الدراسة عن تقديم توصيات عملية للمدربين والمسؤولين عن تطوير كرة السلة للناشئين حول أهمية دمج التدريبات المعرفية في لبرامج التدريبية بهدف تحسين الأداء الرياضي الشامل. كما يمكن ان تساهم الدراسة في اثراء المعرفة العلمية حول العلاقة بين القدرات المعرفية والأداء المهاري في الرياضة // // // // // // // Studysummary: This studyaims to investigate the effectiveness of usingspecialized training modules to improve the levels of concentration and attention amongyouth basketball players (under 17 yearsold) and to explore the relationshipbetweenthese cognitive skills and theirability to make correct decisionsduring the scoringprocess. Basketball isconsidered one of the sports thatrequire high levels of concentration and the ability to pay attention to the changingdetails on the court، in addition to the intuitive speed in makingappropriatedecisions in critical moments. Therefore، the importance of developingthese cognitive aspects amongyoungplayersisevident. The study relies on an experimental design involvingtwo groups: an experimental group receiving training modules focusing on improving concentration and attention، and a control group following a standard training program. Levels of concentration and attention are measuredusingstandardized tests before and afterapplying the training modules. The studyaims to answer the following questions: Does the application of specialized training modules improve the levels of concentration and attention amongyouth basketball playersunder 17 yearsold? Is there a positive relationshipbetween the levels of concentration and attention and the players' ability to make correct decisions in scoring? The studyisexpected to result in practicalrecommendations for coaches and thoseresponsible for the development of youth basketball،regarding the importance of integrating cognitive training into training programs to improveoverallathletic performance. The studymayalsocontribute to enrichingscientificknowledge about the relationshipbetween cognitive abilities and skill performance in sports.
LES-2025-22
Keywords: الوحدات التدريبية; التركيز والانتباه; اتخاذ القرار; ، التهديف